PENJATUHAN HUKUMAN TERHADAP PELAKU PROSTITUSI ONLINE DITINJAU DARI TINDAK PIDANA PERDAGANGAN ORANG (Studi Kasus Putusan Nomor 214/Pid.B/2021/PN.Gpr di Pengadilan Negeri Kabupaten Kediri) - Tustarama, Rekha; Nurbaedah, Nurbaedah (Universitas Islam Kadiri, 2023)
In this study, the sentencing of perpetrators of online prostitution is only for pimps, and for prostitutes and PSK users as witnesses, even though anyone who commits an unlawful act can be held accountable for their actions in order to provide a deterrent effect on the perpetrators. This is where problems arise because of someone committing an unlawful act or a criminal act, but in reality there is a legal vacuum in the substance of sentencing for CSWs and PSK Users. For anyone who violates or commits an unlawful act or a criminal act, especially online prostitution, which is clearly against the law, must be held criminally responsible with strict sanctions for those who commit these criminal acts. For this reason, in this study entitled